PEMBELAJARAN LARI JARAK PENDEK MENGGUNAKAN PENDEKATAN PERMAINAN LARI BOLA KERANJANG PADA SISWA SD - Perani, Ilham; Hidasari, Fitriana Puspa; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakProblems in this study is how the increase in activity of student learning uses the appearance by approach game in the lessons penjaskes class 3 primary schools 25 empaong sekadau upstream. The purpose of this research is to find the study results 3 class public 25 empaong sekadau upstream through learning run of a short distance used the game run basket ball.the methodology it is research class action. Subjects research is a student 3 primary schools 25 empaong about 39 students. Results from study. 1. Usage method of appearance can improve finals student learning 1 the cycle 48,72% while cycle 2 87,18% there has been increasing 38,46%. 2.The athletic learning run of a short distance by using the method appearance approach game can improve the affective students the cycle 1 69,23% while cycle 2 94,87%, there has been increasing 25,64%Â Keywords: The activity of teachers, school tuitionand methods approach game.Â